O culto às celebridades nas redes sociais e sua influência no conteúdo das notícias no jornalismo online do portal globo.com - Carlan, Letícia Amaral (2018)
This research aims to understand how the cult of celebrities in social networks influences the content of news in online journalism at the globo.com portal. For that, it presents in its theoretical body the trajectory of the celebrity, going through subjects like mass communication, cultural industry, the spectacle, the social networks, the hyperspectacle and the notion of public and private. In a second moment, the thesis works with contents such as entertainment and celebrities journalism, relevance principles, newsmaking, newsworthiness and news values, internet, cyberculture, webjournalism, news portals and the globo.com. In addition, it performs, from the content analysis methodology and the categorial analysis technique, the analysis of the 89 stories about celebrities published on the cover of globo.com portal, between October 23 and 29, 2017, constituting a week. The research presents the conclusion that the celebrity journalism of globo.com is characterized by shallow, futile contents that proliferate in society the perfect body pattern.